2021
DOI: 10.3390/curroncol28060423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lung Metastases among 19,321 Metastatic Colorectal Cancer Patients in Eight Countries of Europe and Asia

Abstract: Background: Colorectal cancer is one of the most common malignancies in the Western world, and is responsible for about 10% of annual cancer-related deaths. Especially for UICC stage IV, the probability of survival is significantly reduced. Little is known about risk factors for specific metastatic patterns of colorectal cancer that may also influence patients’ overall survival. Methods: We used data from the IQVIA oncology dynamics (OD) database to determine the prevalence of pulmonary metastases in 19,321 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There is limited biologic rationale suggesting that colon cancer has a predilection for the lungs. 33 Observational data suggesting benefit from lung metastasectomy 25 may also underestimate the potential harms resulting from decreased lung capacity and lung function. 34 In a rare contemporary randomized trial comparing lung resection versus chemotherapy, 5-year OS was 29% in the control group, with no significant improvement in 5-year OS among those receiving lung resection, 35 albeit the sample size was small and the trial was terminated early because of slow recruitment.…”
Section: Colon Cancermentioning
confidence: 99%
“…There is limited biologic rationale suggesting that colon cancer has a predilection for the lungs. 33 Observational data suggesting benefit from lung metastasectomy 25 may also underestimate the potential harms resulting from decreased lung capacity and lung function. 34 In a rare contemporary randomized trial comparing lung resection versus chemotherapy, 5-year OS was 29% in the control group, with no significant improvement in 5-year OS among those receiving lung resection, 35 albeit the sample size was small and the trial was terminated early because of slow recruitment.…”
Section: Colon Cancermentioning
confidence: 99%
“…Therefore, the liver is one of the main sites for metastasis [5]. Venous drainage for the lower 1/3 of the rectum drains via the inferior rectal vein into the systemic circulation, thereby leading to metastasis to the lungs [6].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Among these patients, pulmonary metastasis (PM) accounts account for more than half of patient population in the single and all-site metastasis according the study by Ding et al [1] There are several factors associated with the increased risk of PM of CRC, including tumor staging, lower tumor location, and presence of lymphovascular invasion or perineural invasion. [1,2] Watanabe et al [3] found that the 5-year PM rate after primary tumor R0 resection increased significantly according to initial stage, from 0.6% in stage I, 2.2% in stage II, 9.8% in stage III, to 24.6% in stage IV CRC. Computed tomography (CT) imaging study remains as the primary detection tool for pulmonary metastasis.…”
mentioning
confidence: 99%